2006
DOI: 10.1021/jm061068d
|View full text |Cite
|
Sign up to set email alerts
|

Antitubercular Nucleosides That Inhibit Siderophore Biosynthesis:  SAR of the Glycosyl Domain

Abstract: Tuberculosis (TB) is the leading cause of infectious disease mortality in the world by a bacterial pathogen. We previously demonstrated that a bisubstrate inhibitor of the adenylation enzyme MbtA, which is responsible for the second step of mycobactin biosynthesis, exhibited potent antitubercular activity. Here we systematically investigate the structure activity relationships of the bisubstrate inhibitor glycosyl domain resulting in the identification of a carbocyclic analogue that possesses a K I app value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
165
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(171 citation statements)
references
References 82 publications
4
165
0
2
Order By: Relevance
“…Related aminoacyl sulfamoyl adenosines were shown in previous studies to act as potent inhibitors of NRPS and non-NRPS A domains (94,210). The in vitro and in-culture inhibition efficacy of SAL-AMS was confirmed in further studies (215,303,304,324). Due to the in vitro IC 50 values, which were in the range of the enzyme concentrations used, and the observed noncompetitive inhibition of the analogue with respect to salicylate, SAL-AMS was suggested to be a tight binding inhibitor (91 zyme inhibition were made during further studies with the same compound and several derivatives thereof; however, the compounds were always found to be fully competitive for both ATP and the corresponding aryl acid (44,215,304).…”
Section: Siderophore Pathway Inhibitorsmentioning
confidence: 61%
See 2 more Smart Citations
“…Related aminoacyl sulfamoyl adenosines were shown in previous studies to act as potent inhibitors of NRPS and non-NRPS A domains (94,210). The in vitro and in-culture inhibition efficacy of SAL-AMS was confirmed in further studies (215,303,304,324). Due to the in vitro IC 50 values, which were in the range of the enzyme concentrations used, and the observed noncompetitive inhibition of the analogue with respect to salicylate, SAL-AMS was suggested to be a tight binding inhibitor (91 zyme inhibition were made during further studies with the same compound and several derivatives thereof; however, the compounds were always found to be fully competitive for both ATP and the corresponding aryl acid (44,215,304).…”
Section: Siderophore Pathway Inhibitorsmentioning
confidence: 61%
“…Consequently, SAL-AMS was found to inhibit YbtE with a higher preference (1.8-fold) than DHB-AMS, and DHB-AMS inhibited DhbE preferentially better (1.25-fold) than SAL-AMS (215). A systematic investigation of structure-activity relationships of the glycosyl domain in sulfamate-bridged bisubstrate analogues resulted in the identification of a carbocyclic compound that inhibited MbtA in vitro and M. tuberculosis in iron-deficient cultures with an efficacy comparable to that observed for SAL-AMS (304). It was furthermore suggested that the bisubstrate inhibitors utilize a mycobacterial transporter for crossing the cell envelope.…”
Section: Siderophore Pathway Inhibitorsmentioning
confidence: 93%
See 1 more Smart Citation
“…These differences may be due to the severity of the catabolic condition, since the latter study reported a 40% weight loss due to STZ treatment [83], compared to the ≤5% weight loss achieved in the present study. STZ is known to have toxic effects in mice, where the severity differs depending on the genetic background [84]. Finally, the toxic effects of STZ can extend to the pituitary, since acute STZ treatment leads to blockade of GH secretory vesicle release and somatotrope rupture [85].…”
Section: Discussionmentioning
confidence: 99%
“…S1 in the supplemental material), that specifically targets MbtA by mimicking the salicyl-AMP intermediate (9)(10)(11). In vitro studies have confirmed that salicyl-AMS inhibits MbtA activity and also inhibits M. tuberculosis growth in iron-depleted media (9,12), with the MIC for M. tuberculosis H37Rv found to be 0.5 g/ml in a study with an alamarBlue assay (13). In this study, we have characterized the pharmacokinetics of salicyl-AMS and its therapeutic efficacy in a murine infection model, leading to the first in vivo proof of concept for the use of siderophore biosynthesis inhibitors as novel antibacterials.…”
mentioning
confidence: 96%